The methodical approach to determining the heterogeneity of cognitive function in preschool children requiring correction of speech impediments - N.B. Petrenko (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Introduction. It has been confirmed that children who suffer from speech impediments may experience difficulties in their cognitive activity, limitations in communication, asociality and sense detachment. It is also clear that these children require not only logopedic treatment, but also assistance in developing functions of their cognitive and mental activities. Aims. To identify the case of uniformity lack of cognitive and somatomental functions of 5-6 year old children with speech impediments in a group; to evaluate the method used for this research. Methods. Use estimates of major mental and cognitive activities by means of tests increases the difficulty. Scores from 1 to 10 were given. Such factors as movement coordination, musicality and body plasticity were taken into consideration too. StatSoft STATISTICA10.0. programme was used to run the statistical analysis. Results. The changes of the group with uniformity of physical, cognitive, somatomental and dance abilities were analysed and estimated at the beginning and at the end of the academic year. The results of the claster analysis have shown that the children managed to develop their cognitive and somatomental abilities. Also it was estimated that the level of uniformity has increased in the group. Conclusions. Having done the research we can state that with the help of cluster analysis children with speech impediments can be grouped according to their physical, cognitive, somatomental and dance abilities. With the help of the results of the claster analysis that notifies that the children managed to develop their cognitive and somatomental abilities, we can observe the positivie effects of the suggested dance-cognitive teaching elements in an educational programme.